The business of tourism - Holloway, J. Christopher (New York SAGE Publications Ltd, 2022)
"Tourism as an industry is constantly evolving. Trends and attitudes are susceptible to changes in what people look for in a holiday, which can change within different economic contexts; generational shifts; the political landscape; and most recently, the Covid-19 global pandemic. This popular and comprehensive textbook helps students to not only understand these changes but study them with a critical mindset and historical perspective, desirable for success in assessments.

The text also continues to retain its focus on ‘business’ and the operational aspects of tourism, making it especially useful for students considering a career and/or short term placement in the tourism industry. This 12th edition of The Business of Tourism includes updates to take in changes to the tourism industry and consumption behaviours as a result of: Brexit (the UK’s decision to leave the European Union) the pandemic and its impacts on nature; the operation of attractions; event tourism; hotel chains; transport; and governmental support Sustainability and the reduction of the negative impacts caused by tourism Chris Holloway was a former Professor of Tourism Management at the University of the West of England. Claire Humphreys is a former Head of Department and Principal Lecturer at the University of Westminster. " --
Part 1: Defining and Analysing Tourism and its Impacts
Chapter 1: An Introduction to Tourism
Chapter 2: Tourism in its Historical Context
Chapter 3: The Demand for Tourism
Chapter 4: The Economic Impacts of Tourism
Chapter 5: The Socio-Cultural Impacts of Tourism
Chapter 6: The Environmental Impacts of Tourism
Part 2: The Travel and Tourism Product
Chapter 7: The Structure and Organization of the Travel and Tourism Industry
Chapter 8: Tourist Destinations
Chapter 9: Tourist Attractions
Chapter 10: Event Tourism
Chapter 11: Business Tourism
Chapter 12: The Hospitality Sector: Accommodation and Catering Services
Chapter 13: Tourist Transport by Air
Chapter 14: Tourist Transport by Water
Chapter 15: Tourist Transport on Land
Part 3: Intermediaries in the Provision of Travel and Tourism Services
Chapter 16: The Management of Visitors
Chapter 17: The Structure and Role of the Public Sector in Tourism
Chapter 18: Tour Operating
Chapter 19: Selling and Distributing Travel and Tourism
Chapter 20: Ancillary Tourism Services
Includes bibliographical references and index.
Keywords: Humphreys, Claire; Tourism; Tourism -- Economic aspects